Study on the Utilization of Catechins from Gambir (Uncaria Gambir Roxb) Leaves as Antioxidants Cooking Oil - Daimon Syukri; Fauzan Azima; Rivan Aprialdho (Andalasian International Journal of Agriculture and Natural Sciences (AIJANS), 2022)
Catechins are flavonoid molecules that act as antioxidants in the body. The degradation of palm oil with catechin treatment (400, 200, 100, 50, 0) was investigated in this work (ppm). The goal of this study was to see how efficient catechins are as antioxidants in cooking oil and what the optimal treatment would be for the amount of catechins added. Catechin concentration, antioxidant IC50, free fatty acid, peroxide value, water content, color, and fatty acid profile are all analyzed using GC-MS. Treatment E (400 ppm) was found to be the most effective, with free fatty acid values of 0.45 percent, peroxide value of 5 mek/g, moisture content of 0.89 percent, and color of 95.95 (L*16, 11, a* -1.51, b* 14.51). Catechins can retain three fatty acids in the oil, according to GC-MS analysis: hexadecanoic acid, 9-octadecanoic acid, and heptadecanoic acid.